2021
DOI: 10.29333/iji.2021.14424a
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Instructors’ and Their Implementation of Critical Thinking within Their Lectures

Abstract: A shared learning outcome for baccalaureate programs is for students to think critically and utilize critical thinking skills. However, education in Saudi Arabia seems to has focused more on rote memorization. Critical Thinking (CT), one of several essential skills regarded in college outcomes, has become a vital citizenry skill in Saudi. In this study, the researcher examined whether or not instructors apply CT or use its components in their teaching. This study offers professional development specialists ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…One of the reasons was teachers' readiness to teach critical thinking skills to students (Ismail et al, 2019). Although teachers believed that they taught students critical thinking skills (Alandejani, 2021), the study did not describe how teachers developed students' critical thinking skills. In addition, students were documented to have better learning performance when higher-order thinking skills (HOTS) were explicitly explained to students (Nguyen & Nguyen, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…One of the reasons was teachers' readiness to teach critical thinking skills to students (Ismail et al, 2019). Although teachers believed that they taught students critical thinking skills (Alandejani, 2021), the study did not describe how teachers developed students' critical thinking skills. In addition, students were documented to have better learning performance when higher-order thinking skills (HOTS) were explicitly explained to students (Nguyen & Nguyen, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…However, some researchers found that stakeholders considered college alumni to have shortcomings in critical thinking and problem-solving skills, even though they saw these skills as essential skills that students must have as provisions in living in society (Abidin, 2021). Many higher education institutions still focus on learning by rote methods rather than critical and innovative thinking (Alandejani, 2021).…”
Section: Introductionmentioning
confidence: 99%